MANAGEMENT OF TRADE NETWORK COMPETITIVENESS - BROVKINA, Julia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the processes of managing the competitiveness of trade enterprises that are part of the trade network. A critical analysis of general theoretical positions on assessing the impact of competition in the industry from the perspective of trade enterprises has been made. The most influential competitive forces, which are characteristic of trade enterprises organized on the basis of a network, are determined. It was established that the demand of the main part of the population and the processes of intensifying globalization in trade require the greatest attention in managing the competitiveness of network trade enterprises. The main types of competition in trade are considered and their meaningful characteristics are provided. Special attention is paid to the processes of managing relations with consumers. The necessity of using the approaches of the CRM system as foundation of effective management tools for building a customer loyalty system has been proven. The main results that can be obtained by using CRM analysis tools are defined. It has been established that switching to targeted promotional offers for each client is the most effective means of increasing the effectiveness of managing competitiveness in trade. Loyalty programs have been proven to be an effective competitive tool for each retail network, as they differ in the individuality of their offers.The main types of client privileges in loyalty programs are considered. An analysis of the advantages and disadvantages of existing loyalty programs was carried out in order to determine the strengths and weaknesses in the management of relations with customers of the retail network. It has been established that loyalty bonus programs are the most attractive for both, customers and business owners. From point of customers’ view, their effectiveness manifested in obtaining the necessary offers of goods and services, from point of business owners’ view, these programs allow creating and maintaining a certain number of customers.